Comparative exergoeconomic analysis of indirect and direct bio-dimethyl ether syntheses based on air-steam biomass gasification with CO2 utilization - Nakyai, Teeranun; Patcharavorachot, Yaneeporn; Arpornwichanop, Amornchai; Saebea, Dang (My University, 2020)
Dimethyl ether (DME) is a potential energy source because it is a clean fuel and a crucial intermediate in various chemical productions. The main purposes of this work were to assess and compare the indirect and direct bio-DME syntheses from air-steam biomass gasification with CO2 utilization using energetic, exergetic, and exergoeconomic analyses. The effects of hydrogen to carbon monoxide (H2/CO) and carbon dioxide to carbon monoxide (CO2/CO) ratios on DME yield of the indirect and direct processes were firstly investigated. When considering the combined processes, the results were found that the DME yield of the system with direct DME synthesis is higher than that of the indirect system. Moreover, the energy consumption and exergy destruction of biomass gasification and DME synthesis processes in the indirect system are considerably higher when compared to the direct system. For exergoeconomic analysis, the DME unit cost of the direct system (1.66 $/kg DME) also has lower than that of the system with indirect DME synthesis (2.26 $/kg DME). In addition, the CO2 emission of both systems was also considered. The CO2 emission intensity of the system with direct DME synthesis shows 32.35% lower than the system with indirect DME synthesis.
Keywords: Biomass gasification; CO2 emission; Dimethyl ether; Direct process; Exergoeconomic; Indirect process